Incentivized Time Preferences, Level of Education in a Household and Financial Literacy: Laboratory Evidence - Mudzingiri, Calvin; Mwamba, John W. Muteba; Keyser, Jacobus Nicolaas (Journal of Economics and Behavioral Studies, 2018)
This study investigates the impact of financial literacy, level of education in a household and gender differences on time preferences of students at a university in South Africa. The study relies on a convenient sample of (N=85, female=48%) pursuing a financial literacy course. The study uses a questionnaire, a financial literacy test and a simple binary choice experimental game that elicited individual time discount rate to gather data. Ten percent of the participants were paid (in South African rands) for their time preference choices by way of quota random sampling. Female university students’ individual time discount rate was found to be on average higher than that of their male counterparts, indicating that female university students are generally impatient, especially those with low levels of financial literacy. Our results (using a Negative Binomial Regression analysis and Ordinary Least Squares regression analysis) show that time preferences of university students aresignificantly influenced by highest level of education in the household. The OLS regression model shows that financial literacy, measured using financial literacy test, significantly influence time preferences for all subjects. The study concluded that patience levels among male university students increase as financial literacy increases. Gender, income, age and family size significantly influence time preferences of university students. Highest level of education in a household, financial literacy and gender differences have a bearing on individual time preferences.